Tracking technical debt in agile low code developments - Domingues, Renato; Reis, Miguel; Araújo, Miguel; Marinho, Marcelo; Silva, Mário J. (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2024.28450, 2024)
We present a new practice for tracking technical debt in agile low code developments using new metrics obtained from the development environment. The automated collection of some of the metrics has significantly reduced the effort devoted to collecting project meta-data and makes it possible to run frequent self-assessments and internal audits with little effort. We have obtained evidence that more frequent audits during development help to identify and reduce technical debt, thus improving the quality of delivered software. In addition, we witness a general increase in the quality score of projects developed under the new practice.